Brics As a Geopolitical Security Instrument: Analyzing Russia's Motives in Engaging Africa - Gia Ayu Fita; Wandi Abbas; M. Abdul Hafid Tahir (International Journal of Educational Research & Social Sciences, 2026)
This study analyzes the role of BRICS as a geopolitical security instrument within Russia's broader strategy to expand its influence across Africa amid the ongoing structural transformation of the international order toward multipolarity. Originally established as an economic cooperation forum among developing nations, BRICS has since evolved into a political and strategic platform that functions as an alternative to Western-dominated global institutions. This transformation has become increasingly pronounced in the context of escalating geopolitical tensions between Russia and Western states, particularly in the aftermath of the Ukraine conflict. Employing a descriptive qualitative approach, this study conducts content analysis of policy documents, official statements by Russian officials, international media reports, and communiqués from BRICS summits and the Russia–Africa Summits of 2019 and 2023. The analytical framework draws on the theories of strategic depth and multipolar institutionalism to examine how Russia leverages non-Western multilateral platforms to build cross-regional strategic depth. The findings reveal that Russia has systematically utilized BRICS as an alternative diplomatic channel to consolidate military cooperation, advance energy investment expansion, and construct anti-hegemonic narratives rooted in South–South solidarity across Africa. Through BRICS, Russia positions itself as a strategic partner that upholds the principles of equality, sovereignty, and non-intervention which stands in deliberate contrast to the hierarchical patterns characteristic of Africa–West relations. This article contributes to the international relations literature by broadening the understanding of the role of multipolar institutions in the security strategies of non-Western states, and by demonstrating how BRICS functions as a geopolitical instrument that reconfigures global power dynamics and South–South relations within the context of an emerging multipolar world order.